The influence of aerobic performance on HRR in road cyclists and footballers - Kamil Michalik; Artur Woźniak; Iwona Wierzbicka-Damska (Journal of Education, Health and Sport, 2017)
Introduction. Effective heart rate recovery is associated with higher levels of aerobic performance